God’s Law or Categorical Imperative: on Crusian Issues of Kantian Morality - Kryshtop L.E (Кантовский сборник, 2019)
The ethics of Kant and the ethics of Crusius are strikingly similar. This is manifested in a whole range of principles and concepts. Crusius’ moral teaching hinges on the rigorous moral law which has to be obeyed absolutely, and which makes it different from other prescriptions that are binding only to a relative degree. This is very close to the Kantian distinction between hypothetical and categorical imperatives. Another salient feature of Crusius’ moral teaching is the stress laid on the sphere of internal motives. It is the inner motive that determines the morality of an act, rather than the external form of the act. These and some other features of Crusius’ ethics suggest a possible influence of Crusius on Kant. The possibility of such influence has repeatedly come under close scrutiny. The first works devoted to this problem date to the turn of the nineteenth and twentieth centuries. Pointers to the possibility of such influence are semantic and structural similarities of the two thinkers’ systems. Besides, it is an unchallengeable fact that Kant was fairly familiar with the main theses of Crusian philosophy. Some scholars proceed from the study of Kantian vocabulary. Some of the terms Kant uses, especially in his early works which later formed the basis of his ethical teaching in the critical period, can be traced to the terms of Crusian philosophy. However, an alternative view is that Kant was primarily influenced by Wolffian philosophy (mainly through Baumgarten), while the direct influence of Crusius remains unproven. I examine both points of view and propose my own solution to the problem.